Importance Of Leguminous Crops (In the Example Of "Genetic-1" Variety of Soya Bean) In Increasing Soil Fertility (Texas Journal of Agriculture and Biological Sciences, 2023)
This article provides information on the importance of soybean from leguminous crops in increasing soil fertility. The "Genetic-1" soybean variety was used in the research. According to the results, these three types of soybeans are highly effective in increasing soil fertility.